PERANCANGAN SISTEM INFORMASI SELEKSI KARYAWAN PADA PT. PRAWATHIYA KARSA PRADIPTHA BEKASI - Rakhmah, Astri Hijratul; Alrasyid, Mohamad Ilham (JURNAL LENTERA ICT, 2018)
AbstractInformation technology is one example of a product that is currently developing. Which can help humans in processing and presenting quality information. PT Prawathiya Karsa Pradiptha is one IT company that needs information technology to process candidate employee interview data, therefore an information system is designed that aims to meet those needs. Designing an employee selection information system is needed to design the model first including Use Case, Activity Diagram, ERD, determine relations between tables, Seqeunce Diagrams, Class Diagrams and others. The conclusion obtained in the Design of Employee Selection Information System is to simplify the procedure for submitting additions or changes of employees.Keywords: Information Systems, Information Technology, and Employee Data Processing.